Social Policy for Women in Pakistan - Jafree, Sara Rizvi (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book analyzes the different policy challenges that Pakistani women face and makes regionally relevant policy recommendations across different areas of private and public life, drawing on secondary data from nationally representative surveys and primary data from qualitative interviews. These areas include family safety, housing adequacy, food security and nutritional adequacy, environment and disaster protection, educational development, employment and formal sector inclusion, and health security. The author examines how the history, culture, and political climate of Pakistan have shaped social policy for women, interrogates gaps in social protections for women, and analyzes the limitations for past interventions. This text also looks at collaboration across South Asian countries, as well as using religion, social media, financing, and a new model of governance for comprehensive coverage and sustainable social policy for women. This book will be of interest to scholars, students, and policymakers with focus on women's and gender studies and policy studies in South Asia.
1: Introduction: Protection and Patriarchy. Can They Co-Exist in Pakistan?- 2: Existing Social Protection Services in Pakistan -- 3: Family, Housing, and Social Policy for Women of Pakistan -- 4: Food Security, Nutrition, and Social Policy for Women of Pakistan -- 5: Environmental Challenges, Disaster-risk and Social Policy for Women of Pakistan -- 6: Literacy, Skill Development, and Social Policy for Women of Pakistan -- 7: Employment, Informal Sector Work, and Social Policy for Women of Pakistan -- 8: The Quintuple Health Burden and Social policy for Women in Pakistan -- 9: Overcoming Limitations of Experimental Studies for Better Upscale of Women's Protective Policy -- 10: South Asia's Collaboration for Women's Protection and Social Policy -- 11: Sustainable Comprehensive Social Policy for Women in Pakistan: The Way Forward with Religion, Social-Media, Finances and Governance.
Keywords: Sex; Social policy; Identity politics; Sociology; Social groups; Health; Asia -- Politics and government; Gender Studies; Social Policy; Politics and Gender; Sociology of Family, Youth and Aging; Gender and Health; Asian Politics